Water quality and biological diversity of Budhoholi Wetland, Jhapa, East Nepal - Bhattarai, Bhanu Kumar; Dahal, Diwas (Nepalese Journal of Biosciences, 2017)
The present study deals with the physico-chemical parameters and biological diversity of Budhoholi at Sani-Arjun Municipality -7 Jhapa, from July to October, 2015. The physico-chemical properties of water were within the maximum permissible limit with slight variation in some parameters. The biological diversity was found to be rich. Riparian vegetation consisted of 21 herbs 13 shrubs, 11 trees and 4 climbers, 9 aquatic macrophytes and 21 species of fishes. The overall result of the lake indicated that the lake is not disturbed and is not polluted.